The Right of a Child Outside the Legal Marriage of a Biological Father: The Analysis of Ḥifẓ Al-Nafs as Law `Illat - Abubakar, Ali; Juliana, Juliana; Hasan, Maisyarah Rahmi (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2021)
This article aims to analyze the protection of life (ḥifẓ al-nafs) as the law reason (`illat) of the rights of children outside of legal marriage (ALPS) of biological fathers. Ḥifẓ al-nafs is assumed to be `illat emerging from many neglected ALPS phenomena and resulting in negative stigma and discrimination. This research is a study of Islamic law using the theory of `illat in analyzing the problem of children's rights outside of legal marriage. The research concludes that the presence of the 2010 Constitutional Court decision regarding the civil rights of ALPS with biological fathers reveals new spaces in seeing the nature of ALPS rights. This is different from the fatwa of the Indonesian Ulema Council and classical fiqh (Islamic jurisprudence) arguments, which tend to only link the child to the mother. Based on the Constitutional Court decision, the essence of ALPS rights from biological fathers is limited to civil rights. The responsibility of the biological father to ALPS is in the form of physical and mental support, while denying other rights such as guardianship of marriage; ALPS rights today have been largely abandoned. Thus, the protection/care is necessary. `Illat (the reason of law) in ḥifẓ al-nafs (protection of the life) is real and can be juxtaposed with `illat ḥifẓ al-nasl (protection of heredity). Ḥifẓ al-nasl does not completely fulfill the real requirements of an `illat which can abolish the abandonment of ALPS.